Extent of Adherence to Ethical Codes of Teaching by Primary School Teachers in Nsukka East Local Education Authority - Sunday Ezema, Victor; Odozi Ifelunni, Clara; Chikasiemobi Ugwu, Gloria; Chidobe Okenyi, Emmanuel; Ohabuenyi Abah, George (International Journal of Psychosocial Rehabilitation, 2021)
The study was conducted to assess the extent of adherence to the ethical codes of teaching by primary school teachers in Nsukka East Local Education Authority of Enugu state. Teachers’ Registration Council of Nigeria (TRCN) Act promulgated in Nigeria in 1993 recognizes teaching as a profession. This has given rise to the document “Teachers’ Code of Conduct” which among others stipulates expected teachers’ relationship with colleagues, learners, parents/guardians, employers and the society at large. Most teachers, regrettably, derail from the stipulations of the codes. Two research questions and two hypotheses in line with the specific purposes guided the study. Descriptive research design was adopted for the study. Questionnaire titled “Ethical Codes of Teaching by Primary School Teachers” (ECTPST) was developed by the researchers from literature materials reviewed and the teachers’ code of conduct (2013). Two experts from Measurement and Evaluation and Childhood Education units validated the instrument. Data were collected from all the 225 primary school teachers in the area and were analyzed using mean and standard deviation for the research questions while ttest was used to test the formulated hypotheses. Findings revealed that many teachers administer corporal punishments to pupils and flout different professional conducts with impunity. On the basis of the findings, recommendations were made. Among others, it was recommended that primary school teachers’ activities should be regularly supervised by the Local Education Authority.